(3eGUaMJg GdYGeIs ((3jMi GdOjSWi Hf aNQ GdOjf Hf Ydi Hf TeS GdOjf eMeO GdeGdci s)
(3ChdgG (B:s
(3gPG cJGH jTJed Ydi eG UMaJg GdYGeI , Ch ZdWJ ajg ef cdGe GdYQH GdLGQi ai GdCdaGX hGdcJH jbhd GdYGeI (B: (3dc Ydi EeQI eWGYI HGdcSQ hGdUhGH (B: (3CeQI HGdaJM s
(3BNQgG (B:s
(3GYTQge HcSQ GdTjf E dG GdCQHYg hGdSHYg hGdJSYg aEfc Jbhd ajgG GQHYge GSHYge hGTYge HGdaJM ai gPG cdg fLQ GdcJGH HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdNGeSs
(3GdeNWhW eQJH ai CHhGH Ydi MQha GdeYLes
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B6 - (3U (B7 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B255s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA GdChd (B- (3bSe GdKGfi (B- (3U (B197 s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GddZIs